034 Prospective study of 24-hour levodopa-carbidopa intestinal gel therapy for unresponsive freezing of gait. (29th July 2019) - Nagaratnam, Sai; Chang, Florence Ching-Fen; Tsui, David S; Mahant, Neil; Wolfe, Nigel; Kim, Samuel D; Ha, Ainhi D; Griffith, Jane M; Fung, Victor SC
Abstract : Introduction: We report a prospective, open-label study of 24-hour levodopa-carbidopa intestinal gel (LCIG) as treatment for levodopa 'unresponsive' freezing of gait (FOG) associated with Parkinson's disease. Method: 14 patients with disabling FOG, documented as being levodopa 'unresponsive' following dose cycle assessment, were commenced on continuous 24-hour infusion LCIG therapy with the night-time rate at 50–80% of the daytime infusion rate. Patients underwent baseline and 6 months gait assessments, documentation of their falls frequency and completed FOG questionnaires. The statistical analysis was performed with SPSS 25 software (IBM), using Wilcoxon Signed Rank test and p < 0.05 was set as statistically significant. Result: The fall frequency score reduced from 3 to 1 at 6 months (p=0.011), The FOG questionnaire was 19.3±1.5 at baseline and reduced to 16.0±1.7, at 6 months, respectively (p=0.039). The mean 360 degree turn time was not significantly changed (p=0.77). The daytime LCIG infusion rate was not significantly different before and after 24-hour LCIG therapy (p=0.315). 7 subjects developed visual hallucinations, one required temporary withdrawal from 24-hour LCIG, but as FOG worsened on 16-hour LCIG, he elected to recommence 24-hour LCIG infusion with improvement in FOG with a reduction in falls. 1 subject had postural hypotension which was ameliorated after adjustment of LCIG infusion rate. Conclusion: We provide further evidence that 24-hour LCIG therapy can reduce levodopa 'unresponsive' FOG and associated falls.